El impacto del programa de asistencia social de Argentina "Plan jefes y jefas de hogar" en la pobreza estructural - Pi Alperin, María Noel (El Colegio de México, A.C., 2009)
In this article, we analyze the impact of the Plan Jefes y Jefas de Hogar Desocupados on structural poverty. This social assistance program, introduced in 2002 as a response to the severe economic and political crisis that affected Argentina at the end of 2001, proposes a cash transfer to unemployed heads of households with dependents under the age of 18 or with disabled individuals of any age. We found that the impact of the JJH program on the monetary aspect of poverty is minor and its impact on employment is uncertain, because it is not clear whether it generated new jobs.